Imaging of glutamate in acute carbon monoxide poisoning using chemical exchange saturation transfer - Zheng, Hongyi; Zheng, Wenbin; Liu, Hongkun; Zhang, Gengbiao; Li, Weijia; Zhuang, Jiayan; Guo, Yuelin (Frontiers in Neurology, 2023)
Aims This study adopted the Glutamate Chemical Exchange Saturation Transfer (GluCEST) imaging technique to quantitatively analyze cranial glutamate and discussed the effectiveness of GluCEST values in identifying the pathogenesis of encephalopathy after CO poisoning. Methods The routine MRI and functional MRI scans of two cohorts of subjects (CO group, n = 29; Control group, n = 21) were performed. Between-group comparisons were conducted for GluCEST% in regions of interest (ROI), including the basal ganglia, the thalamus, the frontal lobe, the occipital lobe, the genu of corpus callosum, the cingulate gyrus, and the cuneus. Moreover, an age-stratified subgroup analysis was devised, and a correlational analysis was performed for GluCEST% in each ROI, including the time in coma, Simple Mini-Mental State Examination Scale (MMSE) score, Hamilton Anxiety Scale score, and blood COHb%. Results As compared to the healthy control, the CO group led to significantly increasing GluCEST% in the basal ganglia, the occipital lobe, the genu of the corpus callosum, the cingulate gyrus, and the cuneus (p < 0.05). In the subgroup analysis for age, adult patients had higher GluCEST% in the basal ganglia, the thalamus, the occipital lobe, the cingulate gyrus, and the cuneus compared to healthy adults (p < 0.05). In addition, the correlational analysis of CO-poisoned patients revealed a statistical association between the GluCEST% and the MMSE in the thalamus and the genu of the corpus callosum. Conclusion The GluCEST technique is superior to routine MRI in that it can identify the cerebral biochemical changes sooner after acute CO poisoning, which is significant for our understanding of the role of neurotransmitters in the pathological basis of this disease. Brain injury caused by CO poisoning may be different in adults and children.